Makna Simbolik Tradisi Mandai Ulu Taon di Desa Rambah Tengah Barat Kecamatan Rambah Kabupaten Rokan Hulu - Saripah Aini; T. Romi Marnelly (Penerbit Jurnal Indonesia, 2025)
The aim of this research was to determine the symbolic meaning of the Mandai Ulu Taon tradition. The type of research is qualitative descriptive. Data collection techniques using observation, interviews, documentation. To obtain informants, researchers used the Purposive Sampling technique, namely a method where sampling is determined by certain criteria that are considered relevant. The types and sources of data used are primary and secondary data. In this research, George Herbet Mead's theory of symbolic interactionism is used, which is an important reference, namely Mind (thoughts and thoughts), Self (self), Society (society). The research results show that this tradition is carried out as a symbolic form of prayer as an expression of gratitude to the Almighty Creator for the completion of the post-rice harvest. The symbols in the Mandai Ulu Taon tradition can also be seen in Bagas Rarangan, the last traces of Boru Namora Suri Andung Jati, setting Wednesday, beating the ogung, slaughtering a white village chicken, giving grilled chicken yellow rice, and followed by a meal together using a plate made of banana leaves. This tradition is carried out at the beginning of the year on the Wednesday of the fourth month with a meal together for all the people present.